PENGARUH PEMBERIAN MINUMAN KARBOHIDRAT ELEKTROLIT TERHADAP PRODUKTIVITAS KERJA PADA PEKERJA PEMBUATAN BATU BATA - Ika Nur Saputri; Felix Kasim; Irma Nurianti; Dodi Arif P Siahaan (JURNAL KESMAS DAN GIZI (JKG), 2021)
Work productivity is influenced by many things, one of which depends on the availability of nutrients in the worker's body. In industrial workers, the lack of nutrient consumption that is often experienced is lack of fluids. Workers who worked in hot ambient temperatures for 10 days lost an average of 4.8 - 6 grams of sodium. However, lost body fluids cannot be replaced by simply drinking water during work. This research is a quantitative study with a quasy experimental study design with one group pretest-posttest design which aims to determine the effect of giving electrolyte carbohydrates on work productivity of brick-making workers. The population in this study were all brick-making workers in the drying section, a sample of 42 people who were taken using the total sampling technique. Data were analyzed using Paired Sample t-test with Î± = 0.05. The results showed that there was an effect of giving electrolyte carbohydrate drinks on the work productivity of brick making workers (p value = 0.000). Giving electrolyte carbohydrate drinks can increase energy intake and bind Na + to remain in the cells. Electrolyte carbohydrate drinks replace water and electrolytes lost through sweat during activity and replace carbohydrates used from liver and muscle reserves during activity. Therefore, the owner of the masonry factory is expected to be able to provide water and electrolyte carbohydrate drinks for workers so that workers' fluid needs are met, workers do not experience fatigue and eventually work productivity increases.